Effects of an Early Experience Involving Training in a T-Maze Under either Denial or Receipt of Expected Reward through Maternal Contact - Stamatakis, Antonios; Diamantopoulou, Anastasia; Panagiotaropoulos, Theofanis; Raftogianni, Androniki; Stylianopoulou, Fotini (Frontiers in Endocrinology, 2013)
The mother is the most salient stimulus for the developing pups and a number of early experience models employ manipulation of the mother-infant interaction. We have developed a new model which in addition to changes in maternal behavior includes a learning component on the part of the pups. More specifically, pups were trained in a T-maze and either received (RER rats) or were denied (DER) the reward of maternal contact, during postnatal days 10—13. Pups of both experimental groups learn the T-maze, but the RER do so more efficiently utilizing a procedural-type of learning and memory with activation of the dorsal basal ganglia. On the other hand, the DER experience leads to activation of the hippocampus, prefrontal cortex and amygdala in the pups. In adulthood, male DER animals exhibit better mnemonic abilities in the Morris water maze and higher activation of the hippocampus, while they have decreased brain serotonergic activity, exhibit a depressive-like phenotype and proactive aggressive behavior in the resident-intruder test. On the other hand, male RER animals assume a reactive coping style in this test, showed increased emotionality as well as freezing in the memory test following both contextual and cued fear conditioning.